Improving the systematic approach to pain and sedation management in the ICU by using assessment tools. Issue 11 (27th November 2012) - Wøien, Hilde; Værøy, Henning; Aamodt, Geir; Bjørk, Ida T
<x xml:space="preserve">Abstract</x> Aims and objectives To assess the effects of introducing a systematic approach to pain and sedation management in the ICU. Background Identification of ICU patients' analgesic and sedative needs decreases the risk of complications and the hospital length of stay. Several studies have reported a lack of systematic assessment. Design and methods Three assessment tools were implemented in two Norwegian ICUs in a prospective two‐site study (April–July 2009). Frequency of pain and sedation documentation, the number of days when a sedation level was prescribed, and the amount of analgesics and sedatives used were documented for 958 ICU days in 139 mechanically ventilated patients. Fifty‐five ICU nurses completed a questionnaire on the effects of the assessment tools before and after implementation. Results Patients assessed by the tools had a documented pain score 2·5 times daily and a sedation score three times daily. A sedation level was prescribed for 70% of the total patient days. A documented match between prescribed and reported sedation level was achieved for 27% of the days. Combinations of continuous analgesia and sedation were prescribed with wide therapeutic ranges. Significant improvements were seen in the units' assessment and documentation routines scored by the nurses after the implementation of the tools. Conclusion Although the tools were well accepted, they were not used as frequently as recommended. The proportion of missing written prescriptions and documentation of sedation levels most likely reflects the nurses' and physicians' poorly defined intentions for the prescribed treatment. The tools applied helped nurses to focus on significant signs and symptoms. Relevance to clinical practice Without well‐organised pain treatment and sedation, the risk of oversedation is always present. Our results show that the implementation of tools contributes to a systematic approach of the assessment and treatment of pain and sedation in intensive care.